Bimetal composite bar with surface nano layer and built-in framework and preparation method of bimetal composite bar
Through 3D printing and rotary forging technology, stainless steel-aluminum alloy composite rods with built-in skeletons are formed, and nanolayers are formed using surface mechanical grinding technology, which solves the problem of difficult to take into account both the strength and elongation of aluminum alloys, and achieves high strength and high plasticity and wear resistance, and lightweight material, suitable for multifunctional applications.
Patent Information
- Application Number
- CN202411254439.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-17
AI Technical Summary
The prior art is difficult to maintain its elongation while increasing the strength of aluminum alloys, and it is difficult for stainless steel and aluminum alloy composites to take into account both high strength and high toughness.
3D printing technology is used to prepare stainless steel pipes with built-in porous skeletons, cast 6061 aluminum alloy to form composite rods, and through rotary forging and surface mechanical milling technology, a bimetal composite rod with surface nanolayer and built-in frame is formed.
It realizes the high strength and high plasticity characteristics of stainless steel-aluminum alloy composite materials, and has good fatigue resistance and wear resistance, while reducing the weight of the material and production cost.
Smart Images

Figure CN119140795A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material preparation, and in particular relates to a bimetallic composite rod with a surface nano layer and an internal skeleton and a preparation method thereof. Background Art
[0002] Aluminum and its alloys are the metal materials with the largest usage in structural lightweighting in daily production activities. They have high chemical stability and good plasticity, and have irreplaceable advantages. 6 series aluminum alloys mainly use Si and Mg as alloying elements. They are heat-treated aluminum alloys that rely on Si and Mg precipitation during solid solution treatment as strengthening means. As medium-strength aluminum alloys, they have good formability, high temperature resistance, high strength, corrosion resistance and other excellent properties. They are widely used in building profiles, large structural parts that require good corrosion resistance, trucks, ships, railway vehicle structural parts, ducts, homes, etc. How to improve the strength of lightweight and highly plastic aluminum alloys has become a concern of many scholars. Bulk materials with a grain size of less than 100nm can be prepared by severe plastic deformation (SPD) methods such as high pressure torsion (HPT), equal channel angular extrusion (ECAP), and accumulative roll bonding (ARB). A large number of nanocrystalline grain boundaries, entangled dislocations and alloying elements strengthen the bulk metal, thereby improving its strength. Maowen Liu et al. prepared ultra-high strength nanostructured 2024 aluminum alloy by HPT, and its yield strength increased from 288MPa to 824MPa, and its hardness increased from 123Hv to 234Hv. The yield strength after deformation is about 3 times that before deformation, and the hardness increased by 111Hv compared with that before deformation; however, the elongation at break decreased from 17% to less than 2%. It can be seen that although SPD leads to a significant increase in strength, the elongation also decreases rapidly. Therefore, it is necessary to explore a material processing method that can improve the strength of the material while sacrificing a small amount of elongation.
[0003] Austenitic stainless steel has high toughness, good plasticity, good welding performance, good hot and cold processing performance and corrosion resistance, and is non-magnetic, making it the most widely used stainless steel. Among austenitic stainless steels, 304L stainless steel is widely used in petrochemical, machinery manufacturing and other fields due to its good mechanical properties, oxidation resistance and easy formability.
[0004] A large number of studies have shown that strengthening the surface of the material, changing the size of the surface grain structure, and causing the surface grains to undergo plastic deformation to form a nanolayer can effectively improve the comprehensive performance of the material. Researchers have now explored a variety of surface treatment methods. Surface mechanical grinding (SMGT) can synthesize gradient nano-microstructures on the surface layer of bulk metals. The working principle of this technology is similar to machine tool cutting. After a hard metal ball is pressed into the surface of the material, the metal ball is pushed to make it move relative to the material. The friction between the ball and the surface grains causes the surface of the material to undergo plastic deformation. As the number of grinding increases, the strain also increases. The present invention refines the surface grain size of the composite rod by surface mechanical grinding (SMGT), refines the grains to the nanometer level, improves its strength and hardness, and retains the coarse grain structure of the core to maintain high plasticity. The structural unit of the material changes in a gradient in space, from the coarse grains in the core to the nano-crystals on the surface, so that the material has both high strength and high toughness, and also has good fatigue resistance and wear resistance. Finally, a material processing method was explored that can improve material strength while sacrificing a small amount of elongation, resulting in a stainless steel-aluminum composite rod with high plasticity and high strength. Summary of the invention
[0005] The purpose of the present invention is to provide a bimetallic composite rod with a surface nanolayer and a built-in skeleton and a preparation method. The present invention combines 3D printing technology, casting technology and rotary forging technology. First, 3D printing technology is used to form a 304L stainless steel pipe with an irregular porous skeleton structure, and then 6061 aluminum alloy is cast into the stainless steel pipe to obtain a stainless steel-aluminum alloy composite rod. The stainless steel and the aluminum alloy are tightly combined by rotary forging technology, and then a surface mechanical grinding technology is used to form a nanolayer on the surface of the composite rod, and finally a metal composite material rod with high strength and high plasticity is obtained.
[0006] The technical solution to achieve the purpose of the present invention is: a method for preparing a bimetallic composite rod having a surface nanolayer and an internal skeleton, comprising the following steps:
[0007] Step (1): preparing stainless steel powder and aluminum alloy;
[0008] Step (2): constructing a stainless steel rod model with a built-in porous framework;
[0009] Step (3): using selective laser melting (SLM) to print the model of step (2) to obtain a stainless steel rod with a built-in porous skeleton;
[0010] Step (4): melting 6061 aluminum alloy;
[0011] Step (5): heating the stainless steel rod to a temperature 20-40° C. higher than the melting point of the aluminum alloy, and then casting the aluminum alloy solution into the pores of the skeleton to obtain an initial composite rod;
[0012] Step (6): Use wire cutting to cut off the top of the composite rod with the pouring cup;
[0013] Step (7): heating and heat-insulating the composite rod obtained in step (6) and then performing rotary forging to obtain an elongated composite rod;
[0014] Step (8): The surface of the elongated composite rod is mechanically ground to finally obtain a metal composite rod having a surface nano layer and an internal stainless steel skeleton.
[0015] Furthermore, the stainless steel powder in step (1) is 304L stainless steel powder, and the particle size of the powder ranges from 16 to 52 μm; and the aluminum alloy is 6061 aluminum alloy.
[0016] Furthermore, the structure of the stainless steel rod-shaped model with a built-in porous skeleton constructed in step (2) is: with a pouring cup on the top, the outer shell is in the shape of a pipe, and the internal support is a random porous skeleton structure based on the Thiessen polygon Voronoi structure. The overall structure of the model is controlled by adjusting the two parameters of average pore size D and porosity P, wherein the D parameter range is 1-3 mm, and the P parameter range is 60-80%, and the overall shape is a round rod.
[0017] Furthermore, the process parameters used for the selective laser melting in step (3) are: laser power of 170-260 W, scanning speed of 750-850 mm / s, scanning spacing of 100 μm, laser scanning in a cross-overlapping manner, and an angle of 67° between layers.
[0018] Furthermore, in step (3), the working chamber is filled with nitrogen during the selective laser melting (SLM) forming process.
[0019] Furthermore, step (4) is specifically as follows: using an electromagnetic induction heating furnace to melt the 6061 aluminum alloy at a melting temperature of 570-680° C., adding a refining agent to the alloy to remove slag during the heating process, and after completion, keeping the alloy at the melting temperature for preparation for casting.
[0020] Furthermore, in step (5), the aluminum alloy solution flows into the pores of the skeleton through the conical pouring cup, and the aluminum alloy and the stainless steel skeleton are firmly combined, thereby forming an initial stainless steel-aluminum alloy composite rod.
[0021] Furthermore, in step (7), the initial stainless steel-aluminum alloy composite rod is heated and kept warm at a temperature of 80% of the melting point of the aluminum alloy for a time of 8-10 minutes, and after the heat preservation, a single pressing amount of 5% and a total deformation amount of 20-50% are performed forging to form a grown composite rod.
[0022] Furthermore, in step (8), the grinding indenter is a WC / Co sphere with a diameter of 14 mm, the composite rod rotation speed V1 is 140-160 r / min, the indenter movement speed V2 is 4-6 mm / min, the single indentation depth is 20-50 μm, 5 passes are performed, and the total indentation amount is 100-250 μm; finally, a stainless steel-aluminum alloy composite rod with a built-in skeleton and a uniform surface nanocrystalline layer and a core coarse crystal is obtained.
[0023] A bimetallic composite rod with a surface nano layer and an internal skeleton is prepared by the above method.
[0024] Compared with the prior art, the present invention has the following significant advantages:
[0025] (1) The built-in skeleton in the present invention is a random porous skeleton structure designed based on the Voronoi structure. The porous metal structure is an integrated material that takes into account both structure and function, has excellent specific strength and specific stiffness, and has functions such as energy absorption and shock absorption, multifunctional bearing, sound insulation and heat insulation. The overall structure of the model can be controlled by adjusting the two parameters of the average pore size D and the porosity P. It not only has strong design and controllable structure, but also can maintain better stability when subjected to external force impact.
[0026] (2) The present invention casts the aluminum alloy solution into a porous skeleton of solid-phase stainless steel. The pores that communicate with each other from top to bottom improve the fluidity of the aluminum alloy solution. The two metals are compounded together through fusion, diffusion, and the like to form a metallurgical bond. This solid-liquid composite technology has a simple process, is less constrained by external conditions, has simple process equipment requirements, and has high production efficiency, and has good development prospects.
[0027] (3) Compared with solid metal, printing porous stainless steel structures and casting low-density aluminum alloys on them both make the composite rods further lightweight, achieving a balance between weight reduction and environmental benefits.
[0028] (4) The initial composite rod is further subjected to rotary forging treatment to make the internal solidified aluminum alloy more firmly bonded to the stainless steel skeleton, the internal structure more dense, and further eliminate a small number of defects caused by 3D printing and casting; at the same time, the rotary forging technology can be used to adjust the length of the composite rod, so that its production and application range is wider.
[0029] (5) The main function of the rotary forging technology in the present invention is to firmly bond the internal skeleton of the composite rod and the casting solution, control the length of the composite rod, and the surface nanolayer needs to be completed by surface mechanical grinding; during the surface mechanical grinding process, the ratio of the inner and outer layers of coarse crystals and nano crystals can be adjusted by regulating the amount of pressing and the number of pressing passes, thereby achieving plasticity and strength matching adjustment.
[0030] (6) The laser selective melting technology, casting, rotary forging technology, surface mechanical grinding and other technologies used in the present invention are mature, with low material cost, easy to industrialize, high economic and environmental benefits, and promote the intelligent and green production of rod structural parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of a stainless steel housing model with a built-in skeleton and a pouring cup according to the present invention, wherein (a) is an overall schematic diagram, (b) is a top view, and (c) is a cross-sectional view.
[0032] Figure 2 Schematic diagram of the selective laser melting SLM process adopted in the present invention, wherein (a) is the principle of selective laser melting sample forming, and (b) is a schematic diagram of the laser scanning path.
[0033] Figure 3 Schematic diagram of pouring aluminum alloy solution into the internal skeleton of stainless steel rod.
[0034] Figure 4 Schematic diagram of composite rod wire cutting.
[0035] Figure 5 Schematic diagram of rotary forging.
[0036] Figure 6 Schematic diagram of surface nanostructured process.
[0037] Figure 7 Schematic diagram of the cross section of the gradient structure composite rod of the present invention, (a) is the cross section of the initial composite rod, (b) is the cross section of the elongated composite rod with a smaller cross-sectional area after rotary forging, and (c) is the cross section of the composite rod after surface nano-crystallization. DETAILED DESCRIPTION
[0038] The specific implementation modes of the present invention are further described in detail below, but the implementation modes of the present invention are not limited thereto.
[0039] The present invention selects 304L stainless steel and 6061 aluminum alloy for solid-liquid composite, and uses 3D printing technology to prepare a stainless steel pipe with a random porous skeleton based on a Thiessen polygon (Voronoi) structure. The Thiessen polygon is also called a Voronoi diagram, which is composed of a set of continuous polygons composed of perpendicular bisectors connecting two adjacent points. The distance from any point in a Thiessen polygon to the control point constituting the polygon is less than the distance to the control points of other polygons. The porous skeleton structure designed based on the Voronoi diagram can control the overall structure of the model by adjusting the average pore size and porosity, and has the functions of energy absorption and shock absorption, multifunctional bearing, sound insulation and heat insulation. Then, the aluminum alloy solution is cast into the skeleton pores to realize the solid-liquid composite rod, which can combine the corrosion resistance, wear resistance, high temperature resistance, high strength and hardness of stainless steel with the advantages of low density, lightweight, excellent electrical conductivity and good plasticity of aluminum alloy, and can complement the disadvantages of the two materials, so that the stainless steel-aluminum alloy composite rod has both high strength and good plasticity, and preliminarily solves the problem that the strength and plasticity of aluminum alloy are difficult to take into account.
[0040] Example 1
[0041] Step (1): The experimental materials selected by the present invention are 304L stainless steel powder and 6061 aluminum alloy, and the specific compositions are shown in Table 1 and Table 2. The 304L stainless steel powder is dried by a double cone rotary vacuum dryer to avoid processing problems caused by moisture or oxidation of the powder. The present invention uses 6 series aluminum alloy as the casting solution. In actual production applications, lightweight and tough alloys such as 7 series aluminum alloy or magnesium alloy can also be selected to cast the hollow stainless steel skeleton.
[0042] Table 1 Chemical composition of 304L stainless steel (wt.%)
[0043]
[0044] Table 2 Chemical composition of 6061 aluminum alloy (wt.%)
[0045]
[0046] Step (2): Use 3D modeling software to create a 304L built-in porous skeleton stainless steel pipe model with a pouring cup, such as Figure 1 (a) As shown. The outer diameter of the stainless steel pipe is 30 mm, and the inner diameter is 80% of the outer diameter. The top view and cross-sectional view of the stainless steel skeleton model are shown in Figure 1 As shown in (b)(c).
[0047] Step (3): Convert the 3D model file into stl format, define the height direction of the stainless steel skeleton as the printing direction through the slicing software, the scanning interval is 100 μm, and the number of printing layers is determined according to the part size to obtain the slicing file. Figure 2As shown in (a), the powder spreading scraper spreads the 304L stainless steel powder on the substrate of the working chamber. According to the slice thickness of the model, the laser beam processes the sample part of the current layer at a laser power of 200W and a scanning speed of 750mm / s. After the layer is processed, the working cylinder drops 30μm, and the scraper automatically spreads powder to prepare for the molding of the next layer of sample. The molding-powder spreading-molding process is repeated until the entire sample is formed.
[0048] Step (4): 6061 aluminum alloy is melted at a melting temperature of 650° C. Refining agents are added to the alloy to remove slag during the heating process. After completion, the alloy is kept at the melting temperature to prepare for casting.
[0049] Step (5): Figure 3 As shown, the aluminum alloy solution is poured into the pouring cup on the top of the 3D printed sample. The pouring cup can slow down the impact of the molten metal on the built-in hollow skeleton, so that the aluminum alloy solution can better fill and solidify in the sample. At this time, an initial stainless steel-aluminum alloy composite rod is obtained.
[0050] Step (6): Since the pouring cup is irregular in shape and has a small connection area with the composite rod sample, it cannot withstand severe impact deformation. Therefore, wire cutting is used to cut off the pouring cup portion at the top of the composite rod, such as Figure 4 As shown, it is convenient for the next step of rotary forging.
[0051] Step (7): The composite rod obtained in step (6) is heated and kept warm at a temperature of 450°C for 10 minutes. The purpose of heating and keeping warm is to better combine the built-in skeleton with the aluminum alloy, and then the rotary forging process is performed. The rotary forging schematic diagram is shown in FIG. Figure 5 As shown in Figure 2, the cross-sectional area of the specimen becomes smaller after rotary forging. Figure 7 As shown in (b), the length of the sample also becomes longer, the internal structure becomes denser, and an elongated stainless steel-aluminum alloy composite rod is obtained.
[0052] Step (8): The elongated stainless steel-aluminum alloy composite rod is subjected to surface grinding treatment. The treatment process is as follows: Figure 6 As shown, the grinding indenter is a WC / Co sphere with a diameter of 14 mm, the composite rod rotation speed V1 is 160 r / min, the indenter movement speed V2 is 4 mm / min, the single indentation depth is 50 μm, and the processing is performed 6 times. Figure 7 (c) shows a stainless steel-aluminum alloy composite rod with a hard and complex skeleton and uniform surface nanocrystals and core coarse crystals.
[0053] In summary, the present invention selects 3D printing technology to prepare a stainless steel pipe sample with a hard built-in skeleton; the molten 6061 aluminum alloy solution is cast into the pores of the built-in skeleton of the 3D printed sample, and the stainless steel and the aluminum alloy are connected by solid-liquid composite technology to obtain an initial composite rod; then the inside of the composite rod is made denser and the outside is made more slender by rotary forging to obtain an elongated composite rod; finally, the surface mechanical rolling technology is used to nano-crystallize the surface of the composite rod to obtain a metal composite material rod with matching strength and plasticity.
Claims
1. A method for preparing a bimetallic composite rod having a surface nanolayer and an internal skeleton, characterized in that: The steps include: Step (1): preparing stainless steel powder and aluminum alloy; Step (2): constructing a stainless steel rod model with a built-in porous framework; Step (3): using selective laser melting (SLM) to print the model of step (2) to obtain a stainless steel rod with a built-in porous skeleton; Step (4): melting 6061 aluminum alloy; Step (5): heating the stainless steel rod to a temperature 20-40° C. higher than the melting point of the aluminum alloy, and then casting the aluminum alloy solution into the pores of the skeleton to obtain an initial composite rod; Step (6): Use wire cutting to cut off the top of the composite rod with the pouring cup; Step (7): heating and heat-insulating the composite rod obtained in step (6) and then performing rotary forging to obtain an elongated composite rod; Step (8): The surface of the elongated composite rod is mechanically ground to finally obtain a metal composite rod having a surface nano layer and an internal stainless steel skeleton.
2. The method according to claim 1, characterized in that The stainless steel powder in step (1) is 304L stainless steel powder, and the particle size of the powder ranges from 16 to 52 μm; the aluminum alloy is 6061 aluminum alloy.
3. The method according to claim 2, characterized in that The structure of the stainless steel rod-shaped model with a built-in porous skeleton constructed in step (2) is: with a pouring cup on the top, the outer shell is in the shape of a pipe, and the internal support is a random porous skeleton structure based on the Thiessen polygon Voronoi structure. The overall structure of the model is controlled by adjusting the two parameters of average pore size D and porosity P, where the D parameter range is 1-3 mm, and the P parameter range is 60-80%, and the overall shape is a round rod.
4. The method according to claim 3, characterized in that The process parameters used for the selective laser melting in step (3) are: laser power of 170-260 W, scanning speed of 750-850 mm / s, scanning spacing of 100 μm, laser scanning in a cross-overlapping manner, and an angle of 67° between layers.
5. The method according to claim 4, characterized in that Step (3) During the selective laser melting (SLM) forming process, the working chamber is filled with nitrogen.
6. The method according to claim 5, characterized in that Step (4) is specifically as follows: using an electromagnetic induction heating furnace to melt the 6061 aluminum alloy at a melting temperature of 570-680°C, adding a refining agent to the alloy to remove slag during the heating process, and then keeping the alloy at the melting temperature to prepare for casting.
7. The method according to claim 6, characterized in that Step (5) The aluminum alloy solution flows into the pores of the skeleton through the conical pouring cup, and the aluminum alloy and the stainless steel skeleton are firmly combined, thereby forming an initial stainless steel-aluminum alloy composite rod.
8. The method according to claim 7, characterized in that Step (7) heats and insulates the initial stainless steel-aluminum alloy composite rod at a temperature of 80% of the melting point of the aluminum alloy for 8-10 minutes, and then performs rotary forging with a single reduction of 5% and a total deformation of 20-50% to form a grown composite rod.
9. The method according to claim 8, characterized in that In step (8), the grinding indenter is a WC / Co sphere with a diameter of 14 mm, the composite rod rotation speed V1 is 140-160 r / min, the indenter movement speed V2 is 4-6 mm / min, the single indentation depth is 20-50 μm, 5 passes are processed, and the total indentation amount is 100-250 μm; finally, a stainless steel-aluminum alloy composite rod with a built-in skeleton, a uniform surface nanocrystalline layer and a core coarse crystal is obtained.
10. A bimetallic composite rod having a surface nanolayer and an internal skeleton, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Cited By
Gradient composite material bar containing high-density crimped metal fibers and preparation method
CN119839091A
